ImaginationVellum: Generative-AI Ideation Canvas with Spatial Prompts, Generative Strokes, and Ideation History - Marquardt, Nicolai; Roseway, A.; ROMAT, Hugo; Panda, Payod; Pahud, Michel; Ramos, Gonzalo A.; Drucker, S.; Wilson, Andrew D.; Hinckley, Ken; Henry Riche, Nathalie (User Interface Software and Technology, 2025)
We introduce ImaginationVellum, a multi-modal spatial canvas for early-stage visual ideation and concept sketching with generative AI. The resulting system supports a unique style of human-AI co-creation where the canvas is the prompt. This means that ImaginationVellum employs the entire 2D canvas as an active prompt space, where spatial arrangement, proximity, and composition of diverse content elements—inking, text, images, and intermediate results—steer generative visual outcomes. As a technical probe, ImaginationVellum contributes a set of spatially-grounded direct manipulation tools for iterative visual ideation. In particular, we introduce Generative Strokes—freeform strokes that spatially modulate generation and prompt-parameters (articulated along multiple latent semantic or stylistic dimensions). These techniques afford rapid traversal of design spaces via convergence, divergence, re-composition, blending, and remixing of concepts. We detail the system architecture, design rationale, proximity-dependent intent tags for localized control, and methods for spatial prompting and varying output along spatial gradients. Temporal replay and visualization of provenance make ideation trajectories actionable, turning the design process itself into an artifact that supports reflection-in-action and revisitation of design decisions. We report insights from a preliminary study of how users construct, steer, and revisit ideas using spatial prompts, and discuss tradeoffs in modulating spatially-dependent content generation.